Flow cytometry in the diagnosis of myelodysplastic syndromes and the value of myeloid nuclear differentiation antigen. Issue 3 (17th July 2015) - Bellos, Frauke; Kern, Wolfgang
Abstract : Background: Confirming diagnosis of myelodysplastic syndromes (MDS) is often challenging. Standard diagnostic methods are cytomorphology (CM) and cytogenetics. Multiparameter flow cytometry (MFC) is upcoming in MDS diagnostic work up, comparability and investigator experiences are critical. Myeloid nuclear differentiation antigen (MNDA) in myelomonocytic cells might be expressed more weakly in patients with MDS. The analysis of MNDA may thus improve diagnostic capabilities of MFC in MDS. Methods: Staining methods and antibody combinations for MFC in MDS are outlined, giving details for interpretation of results in regard to dyspoiesis. MFC results are correlated with CM and CG and with survival data. Use of MNDA in MDS diagnostics was evaluated in 239 patients with MDS, AML, other cytopenic conditions, and in 30 negative controls. Results: Strong correlation between findings in CM and MFC was found; MFC results correlated well with those of CG. Patients with higher grades of dysplasia in MFC had shorter overall survival. Percentages of granulocytes and monocytes with diminished MNDA expression (%dimG, %dimM) were higher in patients with MDS and AML. Mean fluorescence intensity (MFI) of MNDA in monocytes was lower in MDS and AML. Cut‐off values for %dimG (12%) and %dimM (22%) as well as for MFI in monocytes (72) were defined discriminating between MDS and non‐MDS. Conclusion: MFC adds significant information on dyspoiesis in the diagnostic work up for MDS and provides prognostic information. MNDA expression can be assessed by MFC and may facilitate evaluation of dyspoiesis when added to MDS MFC panels. © 2015 International Clinical Cytometry Society